INTEGRASI MATERI PENCEGAHAN PERILAKU LGBT DALAM BUKU SISWA PAI DAN BUDI PEKERTI JENJANG SEKOLAH MENENGAH ATAS - Arfan Kurnia Prakasa (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
LGBT behaviour is very worrying because its target is teenagers. When teenagers have become target of its spreading, role of education, especially subjects of Islamic education and character is very important to fortify students are not to be their victims. However, absence of learning materials within student book that are integrated directly with LGBT behavior prevention material becomes an interesting topic to be studied and developed. This research aims to describe some learning materials in student book of Islamic education and character which has a nuance of integration with material of LGBT prevention. Hopefully, this research can be developed in the future. This research uses qualitaitive methode with content analysis. Result of research shows that student book of Islamic education and budi pekerti at Senior High School grade X that have nuance of integration with material of LGBT prevention are (1) Koranic verses and hadith about male and female Moslem dresses, (2) Understanding of adultery, category of adultery, the law for the adulterers, and prohibition of approaching adultery. While in student book of Islamic education and character grade XII are: (1) Command each other advise, (2) Understanding of marriage and unauthorized marriage.